Peranan Wanita dalam Ekonomi Rumah Tangga Petani Sawit (Studi Kasus di Desa Mekar Mulya, Kecamatan Sematu Jaya, Kabupaten Lamandau, Kalimantan Tengah) - Sari, Maya; Purwandari, Istiti; Dinarti, Siwi Istiana (Program Studi Agribisnis INSTIPER Yogyakarta, 2023)
Women often play a role in helping to meet the basic needs of the household. Women who are part of the family like other family members have the same duties and functions in supporting the family, not only in carrying out activities within the family, but in life. The purpose of this research is to find out the economic conditions of the oil palm smallholder households, the extent of the role of women in the household economy, and what factors influence the role of women in the smallholder household economy. This study used a quantitative descriptive method with a simple random sampling technique. The sample is a woman who is a palm oil famer’s wife’s.The OLS Regression methode is used to predict the factors that affec the role of women in the household economy. The results of this study indicate that the economic condition of the households of oil palm farmers, as seen from the average income, is high. The role of women in the smallholder household economy is low. Factors that affect the role of women in the household economy are the number of family dependents, length of work, and land area.